Phenotypic Characterization of Local Chickens in Dekina - Daikwo , I.S.; Okpe, A.A.; Ocheja, J.O. (International Journal of Poultry Science, 2011)
The study was conducted to characterize Local chickens of Dekina based on some phenotypic traits. A total of two thousand four hundred and twenty (2, 420) mature scavenging local chickens were covered. The most predominant plumage colour, shank colour and comb type were brown (41.75%), yellow (40.50%) and single (51%), respectively. Mean bodyweight of mature males (1.32±0.02 kg) was significantly (p<0.05) heavier than the mean of mature females (1.05±0.01 kg). Males were also superior to females in other body parameters measured. Mean egg weight was (28.95±1.21 g). Mean clutch size (7.20±0.20), clutches per hen per year (3.10±0.10) and hatchability of 69.30±1.60% were recorded. Positive and significant (p<0.05) correlation were found between body weight and egg weight and body weight and clutch size. The study showed that the local chickens in Dekina are of the light ecotype class that can be improved by selection and other breeding strategies.